WO2008011957. Substituted benzodithiophenes and benzodiselenophenes for use as semiconductors or charge transport materials in optical, electro-optical or electronic devices. - Heeney,M; Zhang,W; Tierney,S; McCulloch,I (2008)
The invention relates to alkynyl substituted benzodithiophenes and benzodiselenophenes, their use esp. as semiconductors or charge transport materials in optical, electro-optical or electronic devices and to such devices comprising these materials. [on SciFinder(R)]